Investigating the Factors Affecting Academic Decline of Logar University Students - Khpalwak, Mohammad Tahir (Journal of Social Sciences - Kabul University, 2025)
This study aimed to identify the factors contributing to academic decline among Logar University students and assess the extent of their influence. The research population consisted of 1,300 students, of whom 313 were selected as the sample. Data were collected using a questionnaire and analyzed using SPSS version 26. The findings indicate that the academic environment and students’ living conditions have the greatest impact on academic decline, while academic content has the least influence. The highest level of academic decline was observed among fourth-year students and the lowest among third-year students. At the faculty level, the Faculty of Agriculture showed the highest and first level of academic decline, whereas the Faculty of Geology and Mines showed the lowest. Students with illiterate parents were more affected by academic decline than those with literate parents. It is recommended that the university undertake the necessary efforts to improve the academic environment and students’ living conditions.